PENERAPAN MODEL ROLE PLAYING (BERMAIN PERAN) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 026 RAMBAH HILIR KABUPATEN ROKAN HULU - Rini Rini; Zairul Antosa; Munjiatun Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was motivated by the low student learning outcomes, namely with an average 66.4. This research aims to improve learning outcomes IPSsiswa fourth grade SD Negeri 026 Rambah Hilir application of learning models Role playing the number of students 25 people consisting of 16 men and 9 women. Research is a form of class action, the study was conducted in two cycles. The research instrument consists of learning tools and data collection instruments such as observation sheets teacher activity, student activities, and student achievement test IPS. The data presented in this study are: 1. Student learning outcomes can be determined from the average results of study before action is 66.4. In the first cycle class average increased to 77.2 (16.3%) and the second cycle increased to 81.2 (22.3%). Overall at the end of this second cycle of all the indicators and results of social studies students has increased. 2. Activity teacher for applying the learning model Role playing (role playing) increased at each meetings. In the first cycle the first meeting gained an average of 65.0%, and increased in the second meeting be 87.5% with an increase of 22.5%. In the second cycle the first meeting and the second meeting of the 95% increase to 97.5% with an increase of 2.5%. 3. Activity of students during learning with models Role playing (role playing) also increased at each meeting. In the first cycle the first meeting obtained an average score of 67.5% and the second meeting of the increase to be 82.5%. While in the first meeting of the second cycle increased to 87.5% and increased in the second meeting becomes 95.0%. From the results of the study proved that the application of the model Role playing (role playing) can improve learning outcomes IPS fourth grade students SD Negeri 026 Rambah Hilir Kabupaten Rokan Hulu.Keywords: Model Role Playing, Learning achievement of IPS.